Educational Value of Students’ Self-assessment - Vaičiūnienė, Asta; Jucevičienė, Palmira (Pedagogika, 2023)
The article aims to reveal the essence and purposefulness of the educational value of students’ self-assessment in the context of its various perceptions. The essence and application of self-assessment, educational value and its various perceptions, the problematic nature of the evaluation of the study programme and university by the student as a client and its influence on the educational value have been revealed; the possibilities of objectivity of students’ self-assessment and the reasons for subjectivity have been justified. A semi-systematic scientific literature analysis defined self-assessment as a cyclical process of improving learning. The educational value of selfassessment was defined by the understanding the student acquires as: a) future professional – by improving qualification; b) member of the academic community – by strengthening socialization; c) free personality – by a conscious choice to nurture the university values. The student’s selfassessment creates educational value not only for the student but also for the teacher, study programme, and university. The marketization of higher education may facilitate the greater subjectivity of students’ self-assessment and the decrease of its possible educational value. The educational value of self-assessment is ensured by studying in an environment empowering targeted and successful learning. It is highly probable that such an educational value of selfassessment can be achieved in an ecological university.